Immunoreactivity Analysis of Toxoplasma gondii Recombinant Antigen rSAG3 in Sera from Immunized BALB/c Mice and Toxoplasmosis Patients - Mohammad Hossein MOTAZEDIAN; Bahram KAZEMI; Bahador SHAHRIARI; Mojgan BANDEHPOUR; Khadijeh KHANALIHA (Tehran University of Medical Sciences, 2016)
Background: The coccidian protozoa Toxoplasma gondii is an obligate intracellular parasite of humans and other warm-blooded animals. Diagnosis of toxoplasmosis is of considerable medical importance for human, especially pregnant women and immunocompromised individuals. The apply of an Escherichia coli recombinant antigen(s) would be significantly useful in developing standardization of the diagnostic tests and reducing their costs. In this study, immunoreactivity of recombinant SAG3 against sera from immunized mice and human anti-T. gondii IgG positive patients was evaluated by western-blotting and enzyme immunoassay (EIA) in Department of Parasitology and Mycology, School of Medicine, Shiraz University of Medical Sciences in 2013. Methods: Three inbreed BALB/c female mice were obtained. Two mice were injected with rSAG3 and one was remained untreated, as control. Sera from immunized mice and also pooled sera from IgG positive toxoplasmosis cases were evaluated with western-blotting. IgG antibody responses to recombinant SAG3 was measured by indirect ELISA against the negative control group. Results: The rSAG3 protein reacted with sera of immunized mice and sera from patients with anti-Toxoplasma IgG antibodies in western-blot analysis. The result of ELISA showed that, there was marked differences in the absorbance values between the recombinant SAG3 immunized mice and control group. Conclusion: The rSAG3 showed IgG reactivity with sera from immunized mice and anti-Toxoplasma IgG patients.